Lack of Public Administration Ethical Competencies and Human Security - Bulatović, Aleksandra; Korać, Srđan T. (Zbornik Instituta za kriminološka i sociološka istraživanja, 2014)
Deviations from formal mandates, ideological principles or electoral promises have clear ricochet effects on the work of public administration at all its levels. These deviations generate a type of informality that is typically, although crudely, referred to as "administrative corruption". Contemporary human security also reflects the obligation of the state to protect human rights by preventing abuse of public power. By outlining administrative deficit as the result of management modality, lack of ethical competencies as a structural defect in public administration organisation, and administrative evil as a fundamental challenge to the ethical foundation of public administration, the authors point towards key elements for the construction of a functional control mechanism aiming at curbing administrative corruption.